Coming of age: the past, present, and future of quantitative SLA research. (April 2021) - Gass, Susan; Loewen, Shawn; Plonsky, Luke
Abstract: First, we trace the history of second language acquisition (SLA) from early stages in the mid-twentieth century to today. We next consider the status of the field in today's research world with a particular focus on all aspects of methodology and, finally, we take a look at the future and discuss issues related to scientific rigor in light of Open Science.